DISTRIBUTION AND GONAD MATERNITY OF RAZOR CLAM (Solen lamarckii, Chenu 1843) IN INTERTIDAL ZONE OF TELUK LANCAR VILLAGE OF BANTAN SUB DISTRICT, BENGKALIS REGENCY OF RIAU PROVINCE - Anton Akbar Nugraha; Syafruddin Nasution; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe purpose of this research was to know the distribution and maternity of Razor clam’s gonad (Solen lamarckii). This research was held in August 2018 at Teluk lancar village, Bengkalis regency of Riau Province. The research used survey methodology. According to it, the razor clam’s habitat was found in sand substrate that classified as fine sand. The compactness rate of razor clams in its coastal area is 1.2 spesies/m. While, the razor clam’s size rate are bound from 47.9-98.55 mm. Additionally, the most widely gonad maternity was found in box 7.The highest group of razor clam gonad maternity index was <10% as many as 31 individuals. Keywords: Razor Clam, Distribution, Gonad Maternity, Teluk Lancar.